2020
DOI: 10.1016/j.transci.2019.102705
|View full text |Cite
|
Sign up to set email alerts
|

Progress and development of platelet antibody detection

Abstract: Human platelet antibody (HPA) detection is necessary for the diagnosis and therapeutic decisions for refractoriness to platelet transfusions, post transfusion purpura and fetal and neonatal alloimmune thrombocytopenia. In the last four to five decades many new developments, both in knowledge and methods, have increased the quality of platelet serology. However, the quest for the optimal antibody detection method(s) encountered, sometimes unexpected, difficulties. In this review the various aspects concerning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 104 publications
1
22
0
3
Order By: Relevance
“…Alloantibodies develop without clinical symptoms during pregnancy. Details about diagnostics of these antibodies are published by Porcelijn et al [56] in this issue. The only way to prevent severe complications in first pregnancies is by screening and timely antenatal treatment.…”
Section: Antenatal Managementmentioning
confidence: 99%
“…Alloantibodies develop without clinical symptoms during pregnancy. Details about diagnostics of these antibodies are published by Porcelijn et al [56] in this issue. The only way to prevent severe complications in first pregnancies is by screening and timely antenatal treatment.…”
Section: Antenatal Managementmentioning
confidence: 99%
“…Among the 35 pregnancies with an incompatibility between the mother and the fetus, 51% (18/35) were incompatible in HPA‐1, including nine with exclusive incompatibility in the HPA‐1 system (Fig 3). The sensitivity of the detection of anti‐HPA‐1 alloantibodies using a MAIPA test is high (> 90%), 38 but we only detected 57% (8/14) HPA‐1a alloimmunized women in this cohort. This is in agreement with previous studies showing that HPA‐1a alloimmunization occurred in some HPA‐1bb women 39 .…”
Section: Discussionmentioning
confidence: 67%
“…This result underscores the high immunogenicity of HPA-5b incompatibility and the importance of HPA-5 genotyping in pregnancies at risk of FNAIT. Although, the presence of anti-HPA-5b alloantibodies is considered to induce a mild thrombocytopenia, 38 a previous report has shown that in addition to being the second most frequent cause of FNAIT, severe haemorrhages may occur in 23% of cases of fetomaternal incompatibility. 11 Fetomaternal HPA-3 incompatibility was described in 37% (13/35) of cases, including two cases with exclusive incompatibility in this system.…”
Section: Discussionmentioning
confidence: 99%
“…All mothers and fathers and/or cases were genotyped for HPA‐1, ‐3, ‐5 and ‐15 to determine possible fetal–maternal incompatibilities. Platelet antibodies were screened and identified with monoclonal antibody‐specific immobilisation of platelet antigens (MAIPA) 13 and the platelet immunofluorescence test (PIFT) including crossmatching between maternal serum and paternal platelets 14 . FNAIT was confirmed if there was clinical suspicion with neonatal thrombocytopenia (<150 × 10 9 /l) and/or fetal/neonatal bleeding, confirmed HPA incompatibility between the mother and child and the presence of an HPA antibody in the maternal blood sample.…”
Section: Methodsmentioning
confidence: 99%